2006
DOI: 10.1016/j.ijgo.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester operation for uterine prolapse

Abstract: A high degree of acceptance/satisfaction and a low morbidity rate show the Manchester operation to be a good option for the treatment of uterine prolapse in women who wish to keep their uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…After assessment of these reports including reference lists of eligible studies, four studies and two case reports were found with data on 573 women [18][19][20][34][35][36]. All studies were retrospective.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After assessment of these reports including reference lists of eligible studies, four studies and two case reports were found with data on 573 women [18][19][20][34][35][36]. All studies were retrospective.…”
Section: Study Selectionmentioning
confidence: 99%
“…In all other women, the buttock pain resolved within 6 weeks without any intervention. One study reports that the Manchester procedure was associated with hematometra due to cervical stenosis with the need for cervical dilatations in up to 11% of patients [34]. In one woman, after four dilatations of the cervix, an abdominal hysterectomy was performed.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The current literature also documents that the apical support after the Manchester procedure is excellent and the necessity of recurrent surgery for apical prolapse is inconsiderable. 11,12 It is a well known fact that the uterus has a passive role in the uterine prolapse. Therefore, if hysterectomy is being performed this can disrupt the local nerve supply as well as fascial plane and will effect the anatomical relationships of the pelvic organs, however, a literature review concluded that a vaginal hysterectomy is unlikely to cause bowel or bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patientfocused medicine considers some women's wishes to preserve their uterus as a way of maintaining self-esteem, preserving relevant fertility and preventing sexual impairment [12,19].…”
Section: Introductionmentioning
confidence: 99%